Lipid peroxidation products reduce lysosomal protease activities in human retinal pigment epithelial cells via two different mechanisms of action - Krohne, Tim Ulrich; Kämmerer-Gaßler, Elke; Holz, Frank G.; Kopitz, Jürgen (Experimental eye research, 2010)
In age-related macular degeneration (AMD), reduced lysosomal capacity may contribute to lipofuscinogenesis and progressive dysfunction of the retinal pigment epithelium (RPE). We previously demonstrated that lipid peroxidation-related protein modifications inhibit lysosomal degradation of photoreceptor outer segment (POS) proteins in RPE cells. Herein, we investigate the effects of lipid peroxidation products on activities of key RPE lysosomal proteases. In lysosomes isolated from primary human RPE cells, lipid peroxidation products 4-hydroxynonenal (HNE) and malondialdehyde (MDA) exerted a dose-dependent inhibitory effect on cysteine proteases cathepsin B and L, with biologically relevant concentrations of 1 μM resulting in a reduction of enzyme activities by 88-94%. This effect was confirmed in cultured RPE cells. Using mass spectrometry, covalent HNE and MDA adducts were detected in the active center region of inactivated cathepsins. POS previously modified with HNE and MDA likewise caused a dose-dependent reduction of cathepsin B and L activities in isolated lysosomes and, in addition, inhibited the aspartic protease cathepsin D. Our results indicate that lipid peroxidation products in vitro interfere with RPE lysosomal protease activities by two different mechanisms of action: (i) HNE and MDA directly inactivate lysosomal cysteine proteases by covalent binding to the active center; (ii) HNE- and MDA-mediated protein modifications convert proteolytic substrates into competitive inhibitors of lysosomal proteases. Via these mechanisms, lipid peroxidation products may induce lysosomal dysfunction and lipofuscinogenesis in the aging RPE and thus contribute to the pathogenesis of AMD.